Chemical Control of Western Corn Rootworm (Diabrotica virgifera virgifera Le Conte, Coleoptera: Chrysomelidae) in Eastern Romania - Roxana-Georgiana Amarghioalei; Nela Tălmaciu; Monica Herea; Ionela Mocanu; Paula-Lucelia Pintilie; Andreea-Sabina Pintilie; Elena Trotuș; Mihai Tălmaciu (Insects)
This paper aimed to determine the attack caused by WCR (Diabrotica virgifera virgifera Le Conte) and its control by chemical treatments on soil and vegetation. The research was carried out in eastern Romania between 2023 and 2024, where two trials were conducted in the experimental field of the Agricultural Research and Development Station Secuieni—Neamt, where three granular insecticides applied to the soil against larvae and three chemical insecticides used on vegetation against adults were tested. Among the granular insecticides tested, the Force G (tefluthrin 15 g/kg) insecticide stood out with the best results, significantly reducing the number of larvae/plant (1 larva/plant) and, at the same time, the absence of the swan neck symptom was also recorded. Regarding insecticides applied to vegetation, the best results were obtained with the insecticide Inazuma (acetamiprid 100 g/kg + lambda-cyhalothrin 30 g/kg), which recorded a very good efficacy in combating adults of the species (95.4%). In conclusion, applying chemical treatments to soil and vegetation is necessary to control the attack by western corn rootworm (WCR).